Desenvolvimento de um equipamento programável para micro e pequena empresa - Bandeira, Marco Aurelio Garcia (2005)
This essay has as main objective to present an alternative to CNC equipments for small business that need to increase the flexibility of the productive process with little capital as an investment. A bibliography review about the flexible system of production is presented with the necessary information for its development and a history of programmable systems for tool machines. Aiming to reach this objective, the research was developed in seven industries, of small business, located in the city of Santa Maria, RS. This research allowed to identify the difficulties that this industries face to turn its productive system flexible, and the problems from lack of flexibility. Based on this, a model of programmable coordinates table was developed, using parts and available supplies which are commercialized with a low cost, which the main objective is to test its working through a program developed to this purpose.